The Principle of Christocentrism in Catechesis in the Light of Benedict’s XVI Publication Jesus from Nazareth Part I and II - Kostorz, Jerzy (Studia Warmińskie, 2011)
Catechesis oriented towards christocentrism belongs to the basic and most crucial tasks of the Church. Its aim is not only transfering knowledge about Christ and his salvation but also supporting believers in establishing connection with Christ. It requires christocentric orientation in catechesis. The aim of this article is an attempt to reread the principle of christocentrism in catechesis in the light of of Benedist’s XVI reflections gathered in Ist and IInd volume of his book Jesus from Nazareth. Firstly, the essential principle of christocentrism in catechesis will be shown. Next, the main issues connected with understanding of christocentrism in the above mentioned parts of the book Jesus from Nazareth by The Pope Benedict XVI and their usefulness will be described.